Continuous-wave laser annealing of metallic layers for CuInSe2 solar cell applications: effect of preheating treatment on grain growth. Issue 1 (2nd January 2020) - Arnou, Panagiota; Lomuscio, Alberto; Weiss, Thomas P.; Siopa, Daniel; Giraldo, Sergio; Saucedo, Edgardo; Scarpulla, Michael A.; Dale, Phillip J.
Abstract : Ultra-fast thermal annealing of semiconductor materials using a laser can be revolutionary for short processing times and low manufacturing costs. Abstract : Ultra-fast thermal annealing of semiconductor materials using a laser can be revolutionary for short processing times and low manufacturing costs. Here we investigate Cu–In–Se thin films as precursors for CuInSe2 semiconductor absorber layers via laser annealing. The reaction mechanism of laser annealed metal stacks is revealed by measuring ex situ X-ray diffractograms, Raman spectra and composition. It is shown that the formation of CuInSe2 occurs via the formation of Cu x Se/In x Se y binary phases as in conventional annealing routes, despite the entirely different annealing time scale. Pre-alloying the Cu and In metals prior to laser annealing significantly enhances the selenisation reaction rate. Laser annealing for six seconds approaches a near phase-pure material, which exhibits similar crystalline quality to the reference material annealed for ninety minutes in a tube furnace. The estimated quasi Fermi level splitting deficit for the laser annealed material is only 60 meV lower than the reference sample, which implies a high optoelectronic quality.